2013
DOI: 10.1093/ckj/sft033
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of platelet disturbances in haemodialysis patients

Abstract: Patients with mild-to-chronic kidney disease (CKD) exhibit a variety of haemostatic disorders, ranging from an increased clotting tendency and reductions in the levels of natural inhibitors of coagulation to defective fibrinolysis. In addition, platelet (PLT) abnormalities are common. In this minireview, we report on aspects of haemodialysis (HD)-induced PLT activation. It is demonstrated that PLTs from HD patients are exhausted due to repeated stimulation of HD treatment and recurrent release of PLT degranula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
(44 reference statements)
1
16
0
Order By: Relevance
“…Chronic kidney disease (CKD) is a pandemic problem with a global prevalence of 11–13% [ 1 ]. Patients suffering from CKD display a broad spectrum of hemostatic disorders leading on the one hand to increased bleeding tendencies, and to thrombosis on the other [ 2 , 3 ]. Generally, CKD is connected to an increased risk for thrombotic events, including incidence of cerebrovascular disease, myocardial infarction, and pulmonary embolism, as well as postangioplasty or stent thrombosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a pandemic problem with a global prevalence of 11–13% [ 1 ]. Patients suffering from CKD display a broad spectrum of hemostatic disorders leading on the one hand to increased bleeding tendencies, and to thrombosis on the other [ 2 , 3 ]. Generally, CKD is connected to an increased risk for thrombotic events, including incidence of cerebrovascular disease, myocardial infarction, and pulmonary embolism, as well as postangioplasty or stent thrombosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, increased platelet count may reflect a proinflammatory condition with platelet activation [63] . On contrary, Salvati and Liani [64] and Schoorl, Grooteman [19] found that platelet count was decreased in end stage renal failure. This discrepancy was explained by difference in stage of CRF as in their studies, there was an end stage CRF with platelet exhaustion from repeated stimulation by false ligands as fibrinogen fragments.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, an increased platelet reactivity has been reported in patients with CRF [17,18] . On the contrary, Schoorl, Grooteman [19] found that there was a decrease in platelet function and an increase in the risk of hemorrhage in CRF. Moreover, Adams, Irish [20] declared that impaired renal function exposed patients to a higher risk of thrombosis.…”
Section: Introductionmentioning
confidence: 94%
“…17 In hemodialysis patients, repetitive activation of platelets is thought to lead to platelet "exhaustion" and consequent dysfunction. 26 Several studies have been published on bleeding risk with VKA among patients with ESRD (►Table 2). While differing in study design and methodology, most of the larger (> 100 VKA users) studies reported major bleeding rates of 10 per 100 person-years or higher.…”
Section: Safety In Esrdmentioning
confidence: 99%